STRUKTUR DAN FUNGSI MANTRA PENGOBATAN MASYARAKAT MELAYU SAMBAS KECAMATAN SEBAWI - Dayang Azura; Antonius Totok Priyadi; Parlindungan Nadeak (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis thesis is entitled "The Structure and Function of the Mantra of Community Medicine for the Sambas District of Sebawi District". This research is motivated by the desire of researchers to find out the oral literature contained in the Sambas District Sebawi Malay community. The formulation of the problem in this study is how the structure and function of the mantra of treatment of the Sambas Malay community of Sebawi District?. The method in this research is descriptive method. The form of research used is qualitative research and uses a structural approach. The source of data in this study is the mantra of treatment of the Sambas Malay community which consists of 10 data. The data in this study are in the form of words. Data analysis techniques using structural techniques namely by recording and interview. The results of this study found diction were less commonly used in daily life, there are concrete words in each mantra. There are 3 images, 17 rhymes, 3 rhythms, 3 function, and learning implementation plans in the form of Learning Implementation Plan (RPP) on the structure of the even semester X class poetry builder material. Keywords: Function, Structure, , Treatment mantra